ANALYSIS OF PERUM BULOG'S FINANCIAL PERFORMANCE DURING THE COVID-19 PANDEMIC - Ayu, Ari; Rahman, Usman (Paser Institute Of Accounting and Finance, 2024)
This research aims to analyze the financial performance of Perum BULOG during the 2019-2021 Covid-19 pandemic as measured by analyzing liquidity and profitability ratios. The liquidity ratio is measured by the current ratio and quick ratio, while the profitability ratio is measured by return on assets and return on equity. The data used is the 2019-2021 Perum Bulog annual report or financial report obtained from the official Perum Bulog website. This research uses quantitative descriptive methods. The results of data analysis show that the Liquidity Ratio of Perum Bulog is measured using the current ratio and quick ratio. The current ratio in 2019-2021 was at the level of 111.41%, 120.69% and 118.81% respectively. This current ratio calculation position is far below the industry average of 200%. The quick ratio in 2019-2021 was 43.80%, 43.23% and 66.80% respectively. If the quick ratio calculation is compared with the industry average of 150%, the results are far below the industry average or in poor condition. During the Covid-19 pandemic, Perum Bulog's liquidity ratio was in a bad position when measured using the current ratio and quick ratio. Profitability ratios are measured using Return on Assets (ROA) and Return on Equity (ROE). ROA in 2019-2021 was 4.90%, 3.80% and 1.11% respectively. The ROA calculation position is far below the industry average of 30%. ROE for 2019-2021 is -19.50%, 10.00% and 3.00% respectively. The ROE calculation is below the industry average of 40%. During the Covid-19 pandemic, Perum Bulog's profitability ratio was in the bad category when measured using ROA and ROE.